Converting habits of antibiotic use for respiratory tract infections in German primary care (CHANGE-3): process evaluation of a complex intervention - Poß-Doering, Regina; Kühn, Lukas; Kamradt, Martina; Glassen, Katharina; Fleischhauer, Thomas; Kaufmann-Kolle, Petra; Koeppen, M.; Wollny, A.; Altiner, A.; Wensing, Michel (BMC family practice, 2020)
Antimicrobial resistance remains a global challenge. In Germany, the national health agenda supports measures that enhance the appropriate, guideline-oriented use of antibiotics. The study “Converting Habits of Antibiotic Use for Respiratory Tract Infections in German Primary Care (CHANGE-3)” aimed at a sustainable reduction of antimicrobial resistance through converting patterns of prescribing practice and use of antibiotics and an increase in health literacy in primary care patients, practice teams, and in the general public. Embedded in a cluster-randomized trial of a multifaceted implementation program, a process evaluation focused on the uptake of program components to assess the fidelity of the implementation program in the CHANGE-3 study and to understand utilization of its educational components.